Hollow fiber membrane, method for producing the same, and use thereof

By designing and preparing hollow fiber membranes, the problems of material loss and insufficient hydrophilicity in traditional lithium-ion sieves have been solved, achieving a highly efficient and stable lithium extraction process and improving mechanical strength and lithium extraction rate.

CN118437301BActive Publication Date: 2026-11-03GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410482054.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2026-11-03
Estimated Expiration
2044-04-22

AI Technical Summary

Technical Problem

Traditional lithium-ion screening materials are in powder form, which leads to loss and consumption. Furthermore, the hydrophobic properties of organic matter affect the degree of contact between the material and the brine, reducing the lithium extraction efficiency.

Method used

The hollow fiber membrane design incorporates polycaprolactone and lithium-ion sieve powder in the inner layer and a coating of polycaprolactone, chitosan, and polydopamine in the outer layer. Hollow composite fibers are prepared by combining coaxial wet spinning technology to improve mechanical strength and hydrophilicity, and the heating effect under light accelerates lithium extraction.

Benefits of technology

It achieves high mechanical strength and high lithium extraction efficiency, the product does not wear out during long-term use, the photothermal effect improves the lithium extraction rate, and the cycle performance is excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004802493050000111
    Figure BDA0004802493050000111
  • Figure BDA0004802493050000112
    Figure BDA0004802493050000112
  • Figure BDA0004802493050000121
    Figure BDA0004802493050000121
Patent Text Reader

Abstract

The application discloses a hollow fiber membrane and a preparation method and application thereof, and belongs to the technical field of materials. The product is based on the structural design of double hollow composite layer fibers, and mechanical strength and hydrophilic performance of the product can be realized, so that the product will not be obviously lost in the long-term lithium extraction process; meanwhile, the outer layer of the composite layer of the product is further provided with a polydopamine coating, the coating can further improve the mechanical performance of the product, and also has a photo-thermal effect, so that the lithium extraction rate is obviously improved under the condition of light, and the overall lithium extraction effect of the product is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, and in particular to a hollow fiber membrane, its preparation method, and its application. Background Technology

[0002] Lithium metal is an important strategic resource, and lithium extraction from salt lake brine has become a popular method in recent years. Currently, the main lithium extraction device is the lithium-ion screen, which is primarily divided into aluminum-based, manganese-based, and titanium-based screens, each with varying lithium extraction efficiency depending on its application.

[0003] However, traditional lithium-ion screens cannot be recycled and reused, and these screens are mostly in powder form. As the lithium extraction process proceeds, the powdered lithium-ion screens will be lost, so they need to be constantly replenished and replaced to achieve long-term lithium extraction.

[0004] To address this deficiency, powdered lithium-ion sieves are combined with organic materials. The stability and adsorption properties of organic materials as carriers are used to improve the recovery rate and reduce the loss rate. However, this requires that the organic materials be hydrophobic, which reduces the hydrophilicity of the composite lithium-ion sieve material, thereby affecting the degree of contact between the material and the brine and reducing the lithium extraction efficiency. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a hollow fiber membrane. This product is based on a double hollow composite fiber structure design, which can achieve both mechanical strength and hydrophilicity, so that the product will not suffer significant loss during long-term lithium extraction. At the same time, the outer layer of the composite layer is also provided with a polydopamine coating, which can further improve the mechanical properties of the product and also has a photothermal effect. Under light, it generates heat and significantly improves the lithium extraction rate. Overall, the lithium extraction effect of the product is excellent.

[0006] To achieve the above objectives, the technical solution adopted in this paper is as follows:

[0007] A hollow fiber membrane includes hollow composite fibers, wherein the hollow composite fibers comprise an inner layer and an outer layer from the inside out;

[0008] The inner layer comprises polycaprolactone and lithium ion sieve powder;

[0009] The outer layer comprises polycaprolactone, lithium ion sieve powder, and chitosan.

[0010] The outer layer is also coated with a polydopamine coating.

[0011] The hollow fiber membrane of this invention utilizes hollow composite fibers that maintain a sufficiently large specific surface area within their fibrous morphology, ensuring adequate contact with the lithium brine during lithium extraction. The inner layer incorporates polycaprolactone, an organic compound with strong biodegradability, excellent mechanical strength, and adsorption capacity, guaranteeing the product's stability during prolonged lithium extraction and preventing the easy shedding of lithium-ion sieve powder for easy recycling. Furthermore, the outer layer incorporates chitosan, imparting high hydrophilicity and facilitating easier immersion in the lithium brine. Additionally, a polydopamine coating containing catechol structures reacts with the amine groups linked to chitosan to form a catecholamine complex, further enhancing the product's mechanical strength. Moreover, due to the photothermal effect of polydopamine, the coating absorbs light energy and converts it into heat under ambient light, diffusing it to the product surface and ultimately increasing the lithium extraction rate. Compared to traditional polymer-based lithium-ion sieve materials, this method offers significantly higher lithium extraction efficiency.

[0012] Another object of the present invention is to provide a method for preparing the hollow fiber membrane, comprising the following steps:

[0013] Polycaprolactone and a pore-forming agent were formulated into an inner layer solution, and then lithium ion sieve powder was added to the solution and mixed and dispersed to obtain an inner layer spinning solution.

[0014] Polycaprolactone and a pore-forming agent are formulated into an outer layer solution. Then, a chitosan mixture and lithium ion sieve powder are added to the solution and mixed and dispersed to obtain an outer layer spinning solution. The components of the chitosan mixture include chitosan and a pore-forming agent.

[0015] The inner and outer spinning solutions are transferred to a wet spinning device for coaxial wet spinning. The resulting hollow fibers are collected and then subjected to coagulation, water soaking, and drying to obtain a solid fiber membrane.

[0016] The solid fiber membrane is immersed in an alkaline solution of dopamine, and then washed and dried to obtain the hollow fiber membrane.

[0017] In the preparation method of the product described in this invention, two similar components are combined to form an inner layer structure and an outer layer structure by coaxial wet spinning. After the solution evaporates, the resulting fiber can achieve a hollow structure. At the same time, the combination of chitosan and polycaprolactone can effectively prevent chitosan from being converted into electrolyte and causing excessive viscosity. The resulting fiber has good dispersion uniformity. The steps are simple to operate and can realize industrial-scale production.

[0018] In some embodiments, the pore-forming agent is polyethylene glycol.

[0019] More preferably, the weight-average molecular weight of the polyethylene glycol is 400 to 10,000.

[0020] More preferably, the weight-average molecular weight of the polyethylene glycol is 400 to 1000.

[0021] Through the pore-forming effect of polyethylene glycol, more porous structures will appear inside the fibers of the product. These structures are not only more conducive to the loading of lithium ion sieve powder, but also improve the wetting effect of the lithium brine to be extracted. When the molecular weight of polyethylene glycol is 400-1000, the pore-forming effect of the product is even better.

[0022] In some embodiments, the polycaprolactone has a weight-average molecular weight of 50,000 to 90,000.

[0023] More preferably, the polycaprolactone has a weight-average molecular weight of 70,000 to 80,000.

[0024] Polycaprolactones of different molecular weights exhibit varying mechanical strengths and also differ in their adhesion after spinning. Through screening, it was found that when the molecular weight of polycaprolactones is maintained within the aforementioned range, the overall performance of the product is better.

[0025] In some embodiments, the mass ratio of polycaprolactone to pore-forming agent in the inner layer solution is 1:(0.3-1).

[0026] More preferably, the mass concentration of polycaprolactone in the inner layer solution is 10wt%-20wt%.

[0027] In some embodiments, the mass ratio of polycaprolactone to pore-forming agent in the outer layer solution is 1:(0.3-1).

[0028] More preferably, the mass concentration of polycaprolactone in the outer layer solution is 10wt%-20wt%.

[0029] In some embodiments, the degree of acetylation of the chitosan is 75%-85%.

[0030] More preferably, the degree of acetylation of the chitosan is 78%-82%.

[0031] In some embodiments, the weight-average molecular weight of the chitosan is 50,000-200,000.

[0032] In some embodiments, the chitosan mixture has a chitosan concentration of 5 wt% to 15 wt%.

[0033] In some embodiments, the mass ratio of chitosan to pore-forming agent in the chitosan mixture is 1:(0.5-1).

[0034] More preferably, the mass ratio of chitosan mixture to outer layer solution in the outer spinning solution is 1:(0.3-1.2).

[0035] More preferably, the mass ratio of chitosan mixture to outer layer solution in the outer spinning solution is 1:(0.6-1).

[0036] The combination of chitosan and polycaprolactone significantly improves the hydrophilicity of the product, resulting in higher contact capacity with the lithium extraction solution during lithium extraction. However, an excessive proportion of chitosan can lead to a relatively lower mechanical strength. Furthermore, excessive chitosan can increase the viscosity of the outer spinning solution and reduce the fiber formation rate. When the mass ratio of chitosan to polycaprolactone in the outer spinning solution is controlled within the above-mentioned range during the preparation process, the product can achieve a better balance of formation rate, adsorption capacity, and mechanical strength.

[0037] In some embodiments, the chitosan mixture further includes a solvent, wherein the solvent is trifluoroacetic acid.

[0038] In some embodiments, the components of the inner and outer layer solutions further include a solvent, wherein the solvent is 2,2,2-trifluoroethanol.

[0039] In some embodiments, the lithium ion sieve powder in the inner spinning solution has a mass content of 5wt%-45wt%.

[0040] In some embodiments, the mass content of lithium ion sieve powder in the outer spinning solution is 5wt%-45wt%.

[0041] More preferably, the mass content of lithium ion sieve powder in the inner spinning solution and the outer spinning solution is 20wt%-30wt%.

[0042] The lithium-ion sieve powder in the spinning solution does not dissolve in the liquid phase. Therefore, when the content is high, the lithium-ion sieve powder may sink to the bottom or be completely submerged and embedded in polycaprolactone or chitosan. This means that when the product is being processed for lithium extraction, this part of the lithium-ion sieve powder cannot come into contact with the brine to be extracted, resulting in a lower-than-expected lithium extraction capacity.

[0043] In some embodiments, the lithium-ion sieve powder includes H2TiO3 powder and H4Ti5O powder. 12 At least one of the following: powder, λ-MnO2 powder, λ-MnO2·0.3H2O powder, and λ-MnO2·0.5H2O powder.

[0044] In some embodiments, the particle size of the lithium-ion sieve powder is 80nm-400nm.

[0045] In some embodiments, the spinneret of the wet spinning apparatus is a double-layer three-hole spinneret, and the wet spinning apparatus also uses an inner core liquid, which is water, when performing coaxial wet spinning.

[0046] More preferably, the ambient humidity during the coaxial wet spinning process is 40%-60%, and the pressure is 0.01MPa-0.1MPa; the spinning injection flow rate of the inner layer spinning solution and the outer layer spinning solution is 5mL / min-50mL / min, and the spinning injection flow rate of the inner core solution is 5mL / min-50mL / min.

[0047] More preferably, the hollow fibers collected by the coaxial wet spinning process are coagulated in a coagulation solution for 2-6 hours, and the coagulation solution is a sodium hydroxide aqueous solution with a mass concentration of 5wt%-30wt%.

[0048] More preferably, the water immersion temperature is 60-80℃ and the time is 3-10h.

[0049] In some embodiments, the alkaline solution of dopamine is obtained by dispersing dopamine in a solution of tris(hydroxymethyl)aminomethane hydrochloride.

[0050] More preferably, the mass concentration of dopamine in the alkaline solution is 0.01wt%-1wt%.

[0051] In some embodiments, the solid fiber membrane is immersed in an alkaline solution of dopamine for 10-20 hours.

[0052] Another object of the present invention is to provide the application of the hollow fiber membrane in industrial lithium extraction.

[0053] The hollow fiber membrane described in this invention has high mechanical strength and high lithium extraction efficiency. It has excellent sustainable lithium extraction effect for various lithium-containing aqueous phases (such as brine, lithium-containing waste liquid, etc.), high lithium extraction retention rate, and its overall industrial lithium extraction cost-effectiveness is far higher than that of powdered lithium ion sieves or traditional polymer composite lithium ion sieve materials.

[0054] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0055] This invention provides a hollow fiber membrane, its preparation method, and its application. Based on the structural design of a double hollow composite fiber layer, the product can achieve both mechanical strength and hydrophilicity, ensuring that the product does not suffer significant loss during long-term lithium extraction. At the same time, the outer layer of the composite layer is also provided with a polydopamine coating, which can further improve the mechanical properties of the product and also has a photothermal effect. Under light irradiation, the heat generated significantly increases the lithium extraction rate, resulting in excellent overall lithium extraction performance. Attached Figure Description

[0056] Figure 1 This is a schematic cross-sectional view of the hollow fiber obtained during the preparation process of the hollow fiber membrane described in this invention.

[0057] Figure 2 This is a cross-sectional scanning electron microscope image of the hollow composite fibers in the hollow fiber membrane described in this invention. Detailed Implementation

[0058] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0059] Unless otherwise specified, all materials used in the embodiments and comparative examples are commercially available.

[0060] Example 1

[0061] An embodiment of the hollow fiber membrane, its preparation method, and its application according to the present invention, wherein the hollow fiber membrane comprises hollow composite fibers, and the hollow composite fibers comprise an inner layer and an outer layer from the inside out;

[0062] The inner layer comprises polycaprolactone and lithium ion sieve powder;

[0063] The outer layer comprises polycaprolactone, lithium ion sieve powder, and chitosan.

[0064] The outer layer is also coated with a polydopamine coating.

[0065] The method for preparing the hollow fiber membrane includes the following steps:

[0066] (1) Polycaprolactone and pore-forming agent were weighed at a mass ratio of 1:0.4 and added to 2,2,2-trifluoroethanol and stirred for 3 hours to prepare an inner layer solution with a polycaprolactone mass concentration of 15 wt%. Then, lithium ion sieve powder was added to the solution and mixed and dispersed to obtain an inner layer spinning solution. The mass content of lithium ion sieve powder in the inner layer spinning solution was 30 wt%.

[0067] (2) Polycaprolactone and pore-forming agent were weighed at a mass ratio of 1:0.4 and added to 2,2,2-trifluoroethanol and stirred for 3 hours to prepare an outer layer solution with a polycaprolactone mass concentration of 15 wt%. Then, chitosan mixture and lithium ion sieve powder were added to the solution and mixed and dispersed to obtain an outer layer spinning solution. The chitosan mixture was obtained by weighing chitosan and pore-forming agent at a mass ratio of 1:0.6 and adding them to trifluoroacetic acid, heating to 50°C and stirring for 6 hours, with a chitosan mass concentration of 10 wt%. The mass ratio of the outer layer solution to the chitosan mixture was 1:1. The mass content of lithium ion sieve powder in the outer layer spinning solution was 30 wt%.

[0068] (3) The inner and outer spinning solutions are transferred to two feed tanks of the wet spinning device. At the same time, pure water is prepared as the core solution. Coaxial spinning is performed using a double-layer three-hole spinning nozzle. The hollow fibers obtained are collected and then transferred to a 15wt% sodium hydroxide aqueous solution for coagulation for 3 hours, soaked in water at 70°C for 6 hours, and dried to obtain a solid fiber membrane. During the coaxial spinning process, the ambient humidity is 45%, the spinning injection flow rate of the inner and outer spinning solutions is 20 mL / min, the spinning injection flow rate of the core solution is 35 mL / min, and the pressure is 0.05 MPa.

[0069] (4) The solid fiber membrane is immersed in an alkaline solution of dopamine with a mass concentration of 0.5wt% for 15 hours, and then washed and dried to obtain the hollow fiber membrane.

[0070] The polycaprolactone has a weight-average molecular weight of 80,000; the pore-forming agent is polyethylene glycol with a weight-average molecular weight of 400; the lithium-ion sieve powder is H2TiO3 powder; and the chitosan has an acetylation degree of 80% and a weight-average molecular weight of 100,000.

[0071] The alkaline solution of dopamine is prepared by dispersing an appropriate amount of dopamine in a tris(hydroxymethyl)aminomethane hydrochloride solution.

[0072] Example 2

[0073] An embodiment of the hollow fiber membrane and its preparation method and application described in this invention differs from Embodiment 1 only in that, in step (2), the mass ratio of the outer layer solution and the chitosan mixture is 0.6:1.

[0074] Example 3

[0075] An embodiment of the hollow fiber membrane and its preparation method and application described in this invention differs from Embodiment 1 only in that, in step (2), the mass ratio of the outer layer solution and the chitosan mixture is 0.9:1.

[0076] Example 4

[0077] An embodiment of the hollow fiber membrane and its preparation method and application described in this invention differs from Embodiment 1 only in that, in step (2), the mass ratio of the outer layer solution and the chitosan mixture is 0.35:1.

[0078] Example 5

[0079] An embodiment of the hollow fiber membrane and its preparation method and application described in this invention differs from Embodiment 1 only in that, in step (2), the mass ratio of the outer layer solution and the chitosan mixture is 1.15:1.

[0080] Example 6

[0081] An embodiment of the hollow fiber membrane, its preparation method, and its application described in this invention differs from Embodiment 1 only in that the mass content of lithium ion sieve powder in the inner and outer spinning solutions is 20 wt%.

[0082] Example 7

[0083] An embodiment of the hollow fiber membrane, its preparation method, and its application described in this invention differs from Embodiment 1 only in that the mass content of lithium ion sieve powder in the inner and outer spinning solutions is 10 wt%.

[0084] Example 8

[0085] An embodiment of the hollow fiber membrane, its preparation method, and its application described in this invention differs from Embodiment 1 only in that the mass content of lithium ion sieve powder in the inner and outer spinning solutions is 45 wt%.

[0086] Example 9

[0087] An embodiment of the hollow fiber membrane, its preparation method, and its application described in this invention differs from Example 1 only in that the weight-average molecular weight of the polycaprolactone is 60,000.

[0088] Example 10

[0089] An embodiment of the hollow fiber membrane, its preparation method, and its application described in this invention differs from Example 1 only in that the weight-average molecular weight of the polycaprolactone is 70,000.

[0090] Example 11

[0091] An embodiment of the hollow fiber membrane, its preparation method, and its application described in this invention differs from Example 1 only in that the weight-average molecular weight of the polycaprolactone is 85,000.

[0092] Example 12

[0093] An embodiment of the hollow fiber membrane, its preparation method, and its application described in this invention differs from Example 1 only in that the degree of acetylation of the chitosan is 75%, and the weight-average molecular weight is 100,000.

[0094] Example 13

[0095] An embodiment of the hollow fiber membrane, its preparation method, and its application described in this invention differs from Example 1 only in that the degree of acetylation of the chitosan is 85%, and the weight-average molecular weight is 100,000.

[0096] Example 14

[0097] An embodiment of the hollow fiber membrane and its preparation method and application described in this invention differs from Example 1 only in that the mass concentration of the sodium hydroxide aqueous solution in step (3) is 10 wt%.

[0098] Comparative Example 1

[0099] A hollow fiber membrane, its preparation method and application, wherein the hollow fiber membrane comprises hollow composite fibers, and the hollow composite fibers comprise an inner layer and an outer layer from the inside out;

[0100] The inner layer comprises polycaprolactone and lithium ion sieve powder;

[0101] The outer layer comprises lithium-ion sieve powder and chitosan;

[0102] The outer layer is also coated with a polydopamine coating.

[0103] The method for preparing the hollow fiber membrane includes the following steps:

[0104] (1) Polycaprolactone and pore-forming agent were weighed at a mass ratio of 1:0.4 and added to 2,2,2-trifluoroethanol and stirred for 3 hours to prepare an inner layer solution with a polycaprolactone mass concentration of 15 wt%. Then, lithium ion sieve powder was added to the solution and mixed and dispersed to obtain an inner layer spinning solution. The mass content of lithium ion sieve powder in the inner layer spinning solution was 30 wt%.

[0105] (2) The lithium ion sieve powder is added to the chitosan mixture and dispersed to obtain the outer spinning solution; the chitosan mixture is obtained by weighing chitosan and pore-forming agent at a mass ratio of 1:0.6 and adding them to trifluoroacetic acid, heating to 50°C and stirring for 6 hours, and the mass concentration of chitosan is 10 wt%; the mass content of lithium ion sieve powder in the outer spinning solution is 30 wt%;

[0106] (3) The inner and outer spinning solutions are transferred to two feed tanks of the wet spinning device. At the same time, pure water is prepared as the core solution. Coaxial spinning is performed using a double-layer three-hole spinning nozzle. The hollow fibers obtained are collected and then transferred to a 15wt% sodium hydroxide aqueous solution for coagulation for 3 hours, soaked in water at 70°C for 6 hours, and dried to obtain a solid fiber membrane. During the coaxial spinning process, the ambient humidity is 45%, the spinning injection flow rate of the inner and outer spinning solutions is 20 mL / min, the spinning injection flow rate of the core solution is 35 mL / min, and the pressure is 0.05 MPa.

[0107] (4) The solid fiber membrane is immersed in an alkaline solution of dopamine with a mass concentration of 0.5wt% for 15 hours, and then washed and dried to obtain the hollow fiber membrane.

[0108] The polycaprolactone has a weight-average molecular weight of 80,000; the pore-forming agent is polyethylene glycol with a weight-average molecular weight of 400; the lithium-ion sieve powder is H2TiO3 powder; and the chitosan has an acetylation degree of 80% and a weight-average molecular weight of 100,000.

[0109] The alkaline solution of dopamine is prepared by dispersing an appropriate amount of dopamine in a tris(hydroxymethyl)aminomethane hydrochloride solution.

[0110] Comparative Example 2

[0111] A hollow fiber membrane, its preparation method and application, wherein the hollow fiber membrane comprises hollow composite fibers, and the hollow composite fibers comprise an inner layer and an outer layer from the inside out;

[0112] The inner layer comprises polycaprolactone, lithium ion sieve powder, and chitosan.

[0113] The outer layer comprises polycaprolactone, lithium ion sieve powder, and chitosan.

[0114] The outer layer is also coated with a polydopamine coating.

[0115] The method for preparing the hollow fiber membrane includes the following steps:

[0116] (1) Polycaprolactone and pore-forming agent were weighed at a mass ratio of 1:0.4 and added to 2,2,2-trifluoroethanol and stirred for 3 hours to prepare a polycaprolactone solution with a mass concentration of 15 wt%. Then, chitosan mixture and lithium ion sieve powder were added to the solution and mixed and dispersed. The mixture was then divided into two equal parts and named inner spinning solution and outer spinning solution, respectively. The chitosan mixture was obtained by weighing chitosan and pore-forming agent at a mass ratio of 1:0.6 and adding them to trifluoroacetic acid and heating to 50°C and stirring for 6 hours. The mass concentration of chitosan was 10 wt%. The mass ratio of the solution to the chitosan mixture was 1:1. The mass content of lithium ion sieve powder in the inner spinning solution and outer spinning solution was 30 wt%.

[0117] (2) The inner and outer spinning solutions are transferred to two feed tanks of the wet spinning device. At the same time, pure water is prepared as the core solution. Coaxial spinning is performed using a double-layer three-hole spinning nozzle. The hollow fibers obtained are collected and then transferred to a 15wt% sodium hydroxide aqueous solution for coagulation for 3 hours, soaked in water at 70°C for 6 hours, and dried to obtain a solid fiber membrane. During the coaxial spinning process, the ambient humidity is 45%, the spinning injection flow rate of the inner and outer spinning solutions is 20 mL / min, the spinning injection flow rate of the core solution is 35 mL / min, and the pressure is 0.05 MPa.

[0118] (3) The solid fiber membrane is immersed in an alkaline solution of dopamine with a mass concentration of 0.5 wt% for 15 h, and then washed and dried to obtain the hollow fiber membrane.

[0119] The polycaprolactone has a weight-average molecular weight of 80,000; the pore-forming agent is polyethylene glycol with a weight-average molecular weight of 400; the lithium-ion sieve powder is H2TiO3 powder; and the chitosan has an acetylation degree of 80% and a weight-average molecular weight of 100,000.

[0120] The alkaline solution of dopamine is prepared by dispersing an appropriate amount of dopamine in a tris(hydroxymethyl)aminomethane hydrochloride solution.

[0121] Comparative Example 3

[0122] A hollow fiber membrane, its preparation method and application, wherein the hollow fiber membrane comprises hollow composite fibers, and the hollow composite fibers comprise an inner layer and an outer layer from the inside out;

[0123] The inner layer comprises polycaprolactone and lithium ion sieve powder;

[0124] The outer layer comprises polycaprolactone, lithium ion sieve powder, and chitosan.

[0125] The method for preparing the hollow fiber membrane includes the following steps:

[0126] (1) Polycaprolactone and pore-forming agent were weighed at a mass ratio of 1:0.4 and added to 2,2,2-trifluoroethanol and stirred for 3 hours to prepare an inner layer solution with a polycaprolactone mass concentration of 15 wt%. Then, lithium ion sieve powder was added to the solution and mixed and dispersed to obtain an inner layer spinning solution. The mass content of lithium ion sieve powder in the inner layer spinning solution was 30 wt%.

[0127] (2) Polycaprolactone and pore-forming agent were weighed at a mass ratio of 1:0.4 and added to 2,2,2-trifluoroethanol and stirred for 3 hours to prepare an outer layer solution with a polycaprolactone mass concentration of 15 wt%. Then, chitosan mixture and lithium ion sieve powder were added to the solution and mixed and dispersed to obtain an outer layer spinning solution. The chitosan mixture was obtained by weighing chitosan and pore-forming agent at a mass ratio of 1:0.6 and adding them to trifluoroacetic acid, heating to 50°C and stirring for 6 hours, with a chitosan mass concentration of 10 wt%. The mass ratio of the outer layer solution to the chitosan mixture was 1:1. The mass content of lithium ion sieve powder in the outer layer spinning solution was 30 wt%.

[0128] (3) The inner and outer spinning solutions are transferred to two feed tanks of the wet spinning device. At the same time, pure water is prepared as the core solution. Coaxial spinning is performed using a double-layer three-hole spinning nozzle. The hollow fibers are collected and then transferred to a 15wt% sodium hydroxide aqueous solution for coagulation for 3 hours, soaked in water at 70°C for 6 hours, and dried to obtain the hollow fiber membrane. During the coaxial spinning process, the ambient humidity is 45%, the spinning injection flow rate of the inner and outer spinning solutions is 20 mL / min, the spinning injection flow rate of the core solution is 35 mL / min, and the pressure is 0.05 MPa.

[0129] The polycaprolactone has a weight-average molecular weight of 80,000; the pore-forming agent is polyethylene glycol with a weight-average molecular weight of 400; the lithium-ion sieve powder is H2TiO3 powder; and the chitosan has an acetylation degree of 80% and a weight-average molecular weight of 100,000.

[0130] Example 1

[0131] To investigate the performance of the hollow fiber membrane described in this invention, the products obtained in each embodiment and comparative example were subjected to the following tests:

[0132] (1) Mechanical strength test: Each product was stretched to the point of fracture at a rate of 20 mm / min. The curve and cross-sectional area of ​​the sample were recorded. Each sample was tested three times and the average value was taken.

[0133] (2) Adsorption capacity test for the first adsorption: Each product was dispersed in a lithium-containing solution at a solid-liquid ratio of 1g:100mL. The lithium concentration of the solution was 100mg / L and the pH was 9. The solution was then placed in a constant temperature shaker at 25℃ and adsorbed for 3h at a shaking frequency of 150r / min. During this process, the adsorption capacity was increased by 0.5W / cm². 2 Irradiation with 808nm infrared laser, after adsorption is completed, the lithium ion content in the solution is measured and the equilibrium adsorption capacity of the product for the first adsorption is calculated using the following formula;

[0134]

[0135] Q e (mg / g) represents the equilibrium adsorption capacity, C0 and C e The initial and equilibrium concentrations of lithium ions in the solution are (mg / L), respectively; V (L) is the solution volume; and m (g) is the mass of the ion sieve adsorbent added.

[0136] (3) Adsorption capacity retention test: The product after adsorption in step (2) was placed in a constant temperature shaker at 25°C and oscillated at a frequency of 150 r / min, while simultaneously being oscillated at 0.5 W / cm². 2 Irradiation with 808nm infrared laser, followed by desorption with 0.5mol / L hydrochloric acid for 3 hours. One cycle of adsorption-desorption is performed on the desorbed product. This cycle is repeated 5 times. The equilibrium adsorption capacity of the product is calculated using the equilibrium adsorption capacity of the 5th adsorption cycle and the initial equilibrium adsorption capacity.

[0137] Adsorption capacity retention rate (%) = equilibrium adsorption capacity of the 5th adsorption / equilibrium adsorption capacity of the first adsorption × 100%.

[0138] The test results are shown in Table 1.

[0139] Table 1

[0140]

[0141]

[0142] As can be seen from the table, the hollow fiber membrane described in this invention, when applied to lithium extraction operations, not only has high adsorption capacity and high mechanical strength, but also maintains a high level of adsorption capacity retention after multiple adsorption-desorption cycles, demonstrating excellent cycle performance. Figure 1 and Figure 2It can be seen that during product preparation, apart from the core liquid, the two key bonding structures have high bonding strength. After subsequent solidification and drying, the morphology is almost preserved as it was during spinning, without any shedding, deformation, or separation. In contrast, Comparative Example 1 did not introduce polycaprolactone during preparation. That is, the outer layer of the hollow composite fiber in this product is chitosan as a carrier for the lithium-ion sieve powder. Although this product has high hydrophilicity and a high initial adsorption capacity, its mechanical strength is too poor. After repeated adsorption and desorption, the product structure is damaged, which may lead to the loss of lithium-ion sieve powder. Therefore, the product's cyclic adsorption capacity retention rate is only 83.27%. In contrast, Comparative Example 2 used the same raw materials for both the inner and outer layers, introducing hydrophilic chitosan. Therefore, the resulting structure composition is exactly the same. However, this approach further reduces the mechanical strength of the product. Even after repeated adsorption and desorption, the hollow composite fiber in the product breaks and is damaged from the inside. Its damage level is higher than that of Comparative Example 1, so its adsorption capacity retention rate is even lower. Comparative Example 3 did not have a further polydopamine coating on its outer surface. Since the coating itself can undergo a cross-linking reaction with chitosan to improve the overall mechanical strength, the mechanical strength of the product decreased significantly without the coating. In addition, the coating also has the effect of promoting lithium extraction by heating. Therefore, the initial adsorption capacity and adsorption capacity retention rate of Comparative Example 3 were lower than those of the Example products.

[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this article and are not intended to limit the scope of protection of this article. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this article without departing from the essence and scope of the technical solutions of this article.

Claims

1. A hollow fiber membrane, characterized in that, It includes hollow composite fibers, which consist of an inner layer and an outer layer from the inside out; The inner layer comprises polycaprolactone and lithium ion sieve powder; The outer layer comprises polycaprolactone, lithium ion sieve powder, and chitosan. The outer layer is also provided with a polydopamine coating. The method for preparing the hollow fiber membrane is characterized by comprising the following steps: Polycaprolactone and a pore-forming agent were formulated into an inner layer solution, and then lithium-ion sieve powder was added to the solution and mixed and dispersed to obtain an inner layer spinning solution; the mass content of lithium-ion sieve powder in the inner layer spinning solution was 20wt%-30wt%. Polycaprolactone and a pore-forming agent were formulated into an outer layer solution. Then, a chitosan mixture and lithium-ion sieve powder were added to the solution and mixed and dispersed to obtain an outer layer spinning solution. The chitosan mixture consisted of chitosan and a pore-forming agent, with a chitosan concentration of 5 wt%-15 wt%. The mass ratio of the chitosan mixture to the outer layer solution in the outer layer spinning solution was 1:(0.6-1). The lithium-ion sieve powder content in the outer layer spinning solution was 20 wt%-30 wt%. The inner and outer spinning solutions are transferred to a wet spinning device for coaxial wet spinning. The resulting hollow fibers are collected and then subjected to coagulation, water soaking, and drying to obtain a solid fiber membrane. The solid fiber membrane is immersed in an alkaline solution of dopamine, and then washed and dried to obtain the hollow fiber membrane.

2. The hollow fiber membrane as described in claim 1, characterized in that, The weight-average molecular weight of the polycaprolactone is 50,000 to 90,000.

3. The hollow fiber membrane as described in claim 1, characterized in that, In the inner layer solution, the mass concentration of polycaprolactone is 10-20 wt%, and / or, in the outer layer solution, the mass concentration of polycaprolactone is 10 wt%-20 wt%.

4. The hollow fiber membrane as described in claim 1, characterized in that, The degree of acetylation of the chitosan is 75%-85%.

5. The hollow fiber membrane as described in claim 1, characterized in that, The hollow fibers collected by the coaxial wet spinning process are coagulated in a coagulation solution for 2-6 hours. The coagulation solution is a sodium hydroxide aqueous solution with a mass concentration of 5wt%-30wt%.

6. The hollow fiber membrane as described in claim 1, characterized in that, The dopamine concentration in the alkaline solution is 0.01wt%-1wt%, and / or the solid fiber membrane is immersed in the alkaline solution of dopamine for 10-20 hours.

7. The application of the hollow fiber membrane as described in any one of claims 1-6 in industrial lithium extraction.

Citation Information

Patent Citations

  • Preparation method of dopamine composite nano-fiber affinity membrane for adsorbing La3+

    CN103409940A

  • Chitosan-graphene oxide composite fiber, and preparation method and application thereof

    CN112226848A

  • Preparation method of hollow fiber membrane lithium ion adsorbent

    CN116159531A